Integration of well logging and 3D/4D seismic data to map water/gas front saturations in carbonate reservoirs / Mohamed R. Saleh Efnik - Mohamed R. , Saleh Efnik (2018)

(untitled)
With maturing basins and ever deeper and more complex frontiers, the importance of extending the life of and maximizing recovery from producing fields has never been greater. Traditionally, monitoring saturation changes during the field-life has been carried out on well-to-well basis without any information about hydrocarbon distribution between wells. 4D is a seismic method whose value is now recognised worldwide as advanced tool in this respect. While 4D seismic data has been very successful in monitoring hydrocarbon production in clastic reservoirs, its applicability to carbonate reservoirs is still under research. The principal goal of this research is to establish an approach, utilizing time-lapse 4D seismic to detect the maximum change in seismic attributes that could occur as a result of hydrocarbon production in complex carbonate reservoirs. A rock physics test, using tri-axial cell, was successfully conducted on 56 core samples from four wells from the study area to assess pressure effect on seismic reflectivity between the “base” and “monitoring” surveys (acquired with same parameters in five years). The change in pressure would produce 3% change in reflection coefficient (Rp) which is unlikely to have any significant 4D anomalies. Seismic rock properties analysis was carried out on well log data from six wells from the study area to establish the maximum change in seismic parameters that could occur as a result of hydrocarbon and to relate these parameters to assessment of seismic detectability. When the reservoir fluid changes, the reservoir velocity also changes causing changes in the seismic wave to take place as it travels through the reservoir. The Two-Way-Travel (TWT) time is reduced (-ve values) in case of oil while in case of gas the TWT is increased (+ve values). It was found that the change in reflection coefficient and amplitude, when oil replaced by water, for different reservoirs ranges from 15% to 17% and 9% to 16% respectively. When the oil is fully replaced by gas (100 gas saturation), these changes are 10 to 11% for reflection coefficient and 8 to 9% for amplitude. The monitoring survey is subtracted from the base survey and the difference volumes are visually analysed. The difference in seismic response between the base and monitoring volumes is related to fluid saturation changes. In this research, the capability of 4D timelapse technique to monitor fluid saturation in carbonate reservoirs due to fluid changes in the reservoir has been proven. A number of new approaches that have been adopted are attributed to the success of this technique, first time in carbonate reservoirs. The application of sparse spike inversion on the 4D response was used to attenuate random noise and increase the vertical resolution without harming the primary 4D events. To attenuate the noise further and increase the signal-to-noise ratio, a mild soft spatial constraint was used. This helped to stabilize the low frequencies and improve lateral continuity thus attenuates and supresses the effect of random noise by inverting a 3D set of neighbouring traces simultaneously rather than the whole 3D model as previously performed. Furthermore, the seismic data was re-sampled from 4ms to 1ms to allow the inversion to place interfaces (zones) in their correct positions. Reservoir simulation model consists of properties such as facies, porosity, permeability and water saturation in a cell and layer basis. It is used to predict the field performance, forecast the reservoir behaviour overtime and identify best development scenarios to better sweep hydrocarbon from the reservoir. The simulation model was inverted (Sim2Seis approach) to acoustic impedance (AI), followed by application of the above filtering techniques to improve the signal-to-noise ratios, then compared to the AI that is inverted from the 4D time-lapse seismic response to validate the results. The validation process is complemented by corendering technique which was used to compare and validate 4D seismic responses using simulation models, field data to identify area where they match and where not. 4D bodies map that show comparison between 4D seismic response and simulation model was constructed. Around 70% of 4D response anomalies have been confirmed with the simulation model and well data. The new approaches that were used to enhance the 4D response and the calibration of these responses with reservoir simulation model and production and well log data has demonstrated the viability of 4D time-lapse to detect the maximum change in seismic attributes that occur over time in carbonate reservoirs due to hydrocarbon production. Carbonate reservoirs contribute to more than two-thirds of world’s hydrocarbon production. Therefore, effective monitoring of these reservoirs using time-lapse technique will help to optimize Enhanced Oil Recovery (EOR), used as reservoir management tool to improve the recovery factor of the field and help optimize field development scenarios and locate by-pass hydrocarbons for future drilling.